Genetic and clinical diagnosis in non-syndromic hearing loss. (September 2013) - Sommen, Manou; van Camp, Guy; Boudewyns, An
Abstract: Once a diagnosis of unilateral or bilateral congenital hearing loss is established in an infant by age-specific auditory testing, a search for an underlying aetiological diagnosis is required. A rational and cost-efficient aetiological work-up requires a basic knowledge about risk factors and the most common reasons for congenital hearing loss. Both genetic and environmental factors each account for about half of the causes. Among the environmental factors, perinatal insults and congenital infections, especially congenital cytomegalovirus infection, should be considered. Imaging is required to exclude structural inner ear anomalies that may occur as an isolated entity, be part of a syndrome and/or may have therapeutic implications when a surgical intervention for the hearing loss by means of cochlear implantation is envisaged. Genetic testing is an integral part of the aetiological work-up. Although more than 47 causative genes have been identified for the non-syndromic forms of hearing loss alone, diagnostic application of the scientific progress has lagged behind, because screening all the known causative genes for hearing loss in one patient with current technology would be extremely expensive. Consequently, current routine DNA diagnostic testing for non-syndromic hearing loss is restricted to one or two of the most common causative genes, which identifies the responsible gene in only 10–20% of cases. However, on the basis of audiometric information (frequencies affected, thresholds), age of onset, imaging results or other clinical information, specific genes should be analysed. The aims of the present paper are to propose a rational and scientifically valid diagnostic strategy for an aetiological work-up of congenital hearing loss including an overview of the current DNA diagnostics as well as a brief look into the future.